2017
DOI: 10.1002/acn3.445
|View full text |Cite
|
Sign up to set email alerts
|

Neurite dispersion: a new marker of multiple sclerosis spinal cord pathology?

Abstract: ObjectiveConventional magnetic resonance imaging (MRI) of the multiple sclerosis spinal cord is limited by low specificity regarding the underlying pathological processes, and new MRI metrics assessing microscopic damage are required. We aim to show for the first time that neurite orientation dispersion (i.e., variability in axon/dendrite orientations) is a new biomarker that uncovers previously undetected layers of complexity of multiple sclerosis spinal cord pathology. Also, we validate against histology a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
243
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 258 publications
(287 citation statements)
references
References 51 publications
(78 reference statements)
33
243
1
Order By: Relevance
“…Our observation suggests that the neurite loss is the main pathological process, but this needs further histological confirmation. We note however that Grussu et al 32 have demonstrated, in the tissue specimen of multiple sclerosis, that ODI correlated well with histological measures of neurite orientation dispersion, and NDI with histological measures of neurite density.…”
Section: Discussioncontrasting
confidence: 45%
“…Our observation suggests that the neurite loss is the main pathological process, but this needs further histological confirmation. We note however that Grussu et al 32 have demonstrated, in the tissue specimen of multiple sclerosis, that ODI correlated well with histological measures of neurite orientation dispersion, and NDI with histological measures of neurite density.…”
Section: Discussioncontrasting
confidence: 45%
“…An unexpected result is the lower ODI values found in lesional tissue compared with HC WM and NAWM in MS subjects. However, a recent ex vivo combined MRI and pathological study found a similar trend of decreased ODI in MS spinal cord lesions (Grussu et al, 2015). Nevertheless, the ODI results in the lesions should be interpreted with caution given that, in the presence of severe axonal loss (as shown by low NDI), the degree of dispersion was estimated from only a small fraction of the signal in the tissue, which might have resulted in numerical instabilities in the NODDI model fit.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, there is currently limited histopathological evidence to specifically validate NODDI metrics in human cortical grey matter. However, NODDI‐derived indices have been shown to closely correlate with histological counterparts on postmortem examination in the context of multiple sclerosis spinal cord lesions (Grussu et al, ). In addition, some discrepancies between the NODDI model and emerging multi‐shell diffusion techniques that utilize linear and spherical tensor encoding (as opposed to the single diffusion encoding approach of NODDI) have been reported (Lampinen et al, ).…”
Section: Discussionmentioning
confidence: 99%